Multi Perspectives on Play Based Curriculum Quality Standards in the Center Learning Model - Hapidin; Meilanie, R. Sri Martini; Syamsiatin, Eriva (Jurnal Pendidikan Usia Dini, 2020)
Playing curriculum development based on early childhood learning is a major issue in international early childhood education discussions. This study aims to look at the concepts and practices of play-based curriculum in early childhood education institutions. The study uses qualitative methods with the CIPP model program evaluation on play-based curriculum. Data collection techniqueswere carriedout using participatory observation, document studies and interviews. Participants are early childhood educators, early childhood and parents. The results found that the play-based curriculum has not yet become the main note in the preparation and development of concepts and learning practices in early childhood. Play-based curriculum quality standards have not provided a solid and clear concept foundation in placing play in the center of learning models. Other findings the institution has not been able to use the DAP (Developmentally Appropriate Practice) approach fully, and has not been able to carry out the philosophy and ways for developing a curriculum based on play. However, quite a lot of research found good practices implemented in learning centers in early childhood education institutions, such as develop children's independence programs through habituation to toilet training and fantasy play. Keywords: Play Based Curriculum, Center Learning Model, Curriculum Quality Standards, Early Childhood Education Reference Alford, B. L., Rollins, K. B., Padrón, Y. N., & Waxman, H. C. (2016). Using Systematic Classroom Observation to Explore Student Engagement as a Function of Teachers’ Developmentally Appropriate Instructional Practices (DAIP) in Ethnically Diverse Pre- kindergarten Through Second-Grade Classrooms. Early Childhood Education Journal, 44(6), 623–635. https://doi.org/10.1007/s10643-015-0748-8 Ali, E., Kaitlyn M, C., Hussain, A., & Akhtar, Z. (2018). the Effects of Play-Based Learning on Early Childhood Education and Development. Journal of Evolution of Medical and Dental Sciences, 7(43), 4682–4685. https://doi.org/10.14260/jemds/2018/1044 Ashiabi, G. S. (2007). Play in the preschool classroom: Its socioemotional significance and the teacher’s role in play. Early Childhood Education Journal, 35(2), 199–207. https://doi.org/10.1007/s10643-007-0165-8 Berk, L. E., & Meyers, A. B. (2013). The role of make-believe play in the development of executive function. American Journal of Play, 6(1), 98–110. Bodrova, E., Germeroth, C., & Leong, D. J. (2013). Play and Self-Regulation: Lessons from Vygotsky. American Journal of Play, 6(1), 111–123. Retrieved from http://eric.ed.gov/?id=EJ1016167 Chien, N. C., Howes, C., Burchinal, M., Pianta, R. C., Ritchie, S., Bryant, D. M., ... Barbarin, O. A. (2010). Children’s classroom engagement and school readiness gains in prekindergarten. Child Development, 81(5), 1534–1549. https://doi.org/10.1111/j.1467-8624.2010.01490.x Cortázar, A. (2015). Long-term effects of public early childhood education on academic achievement in Chile. Early Childhood Research Quarterly, 32, 13–22. https://doi.org/10.1016/j.ecresq.2015.01.003 Danniels, E., & Pyle, A. (2018). Defining Play-based Learning. In Encyclopedia on Early Childhood Development (Play-Based, pp. 1–5). OISE University of Toronto. Ejuu, G., Apolot, J. M., & Serpell, R. (2019). Early childhood education quality indicators: Exploring the landscape of an African community perspective. Global Studies of Childhood. https://doi.org/10.1177/2043610619832898 Faas, S., Wu, S.-C., & Geiger, S. (2017). The Importance of Play in Early Childhood Education: A Critical Perspective on Current Policies and Practices in Germany and Hong Kong. Global Education Review, 4(2), 75–91. Fisher, K. R., Hirsh-Pasek, K., Newcombe, N., & Golinkoff, R. M. (2013). Taking shape: Supporting preschoolers’ acquisition of geometric knowledge through guided play. Child Development, 84(6), 1872–1878. https://doi.org/10.1111/cdev.12091 Hennessey, P. (2016). Full – Day Kindergarten Play-Based Learning : Promoting a Common Understanding. Education and Early Childhood Development, (April), 1–76. Retrieved from gov.nl.ca/edu Holt, N. L., Lee, H., Millar, C. A., & Spence, J. C. (2015). ‘Eyes on where children play’: a retrospective study of active free play. Children’s Geographies, 13(1), 73–88. https://doi.org/10.1080/14733285.2013.828449 Jay, J. A., & Knaus, M. (2018). Embedding play-based learning into junior primary (Year 1 and 2) Curriculum in WA. Australian Journal of Teacher Education, 43(1), 112–126. https://doi.org/10.14221/ajte.2018v43n1.7 Kathy, E. (2016). Play-based versus Academic Preschools. Parent Cooperative Preschool International, 1–3. Klenowski, V., & Wyatt-Smith, C. (2012). The impact of high stakes testing: The Australian story. Assessment in Education: Principles, Policy and Practice, 19(1), 65–79. https://doi.org/10.1080/0969594X.2011.592972 Martlew, J., Stephen, C., & Ellis, J. (2011). Play in the primary school classroom? The experience of teachers supporting children’s learning through a new pedagogy. Early Years, 31(1), 71– 83. https://doi.org/10.1080/09575146.2010.529425 Mcginn, A. (2017). Play-based early childhood classrooms and the effect on pre-kindergarten social and academic achievement (University of Northern Iowa). Retrieved from https://scholarworks.uni.edu/grp Miller, E., & Almon, J. (2009). Crisis in the Kindergarten. Why children need to to Play in School. In Alliance for childhood. Retrieved from www.allianceforchildhood.org. Özerem, A., & Kavaz, R. (2013). Montessori Approach in Pre-School Education and Its Effects. Tojned The Online Journal of New Horizons in Education, 3(3), 12–25. Pendidikan, K., & Kebudayaan, D. A. N. Menteri Pendidikan Dan Kebudayaan Republik Indonesia Nomor 137 Tahun 2013 Tentang Standar Nasional Pendidikan Anak Usia Dini. , (2015). Peng, Q. (2017). Study on Three Positions Framing Kindergarten Play-Based Curriculum in China: Through Analyses of the Attitudes of Teachers to Early Linguistic Education. Studies in English Language Teaching, 5(3), 543. https://doi.org/10.22158/selt.v5n3p543 Pyle, A., & Bigelow, A. (2015). Play in Kindergarten: An Interview and Observational Study in Three Canadian Classrooms. Early Childhood Education Journal, 43(5), 385–393. https://doi.org/10.1007/s10643-014-0666-1 Pyle, A., & Danniels, E. (2017). A Continuum of Play-Based Learning: The Role of the Teacher in Play-Based Pedagogy and the Fear of Hijacking Play. Early Education and Development, 28(3), 274–289. https://doi.org/10.1080/10409289.2016.1220771 Reid, A. (2009). Is this a revolution?: A critical analysis of the Rudd government’s national education agenda. Curriculum Perspectives, 29(3), 1–13. Ridgway, A., & Quinones, G. (2012). How do early childhood students conceptualize play-based curriculum? Australian Journal of Teacher Education, 37(12), 46–56. https://doi.org/10.14221/ajte.2012v37n12.8 Rogers, S., & Evans, J. (2007). Rethinking role play in the Reception class. Educational Research, 49(2), 153–167. https://doi.org/10.1080/00131880701369677 Samuelsson, I. P., & Johansson, E. (2006). Play and learning-inseparable dimensions in preschool practice. Early Child Development and Care, 176(1), 47–65. https://doi.org/10.1080/0300443042000302654 Saracho, O. N. (2010). Children’s play in the visual arts and Literature. Early Child Development and Care. Saracho, O. N. (2013). An integrated play-based curriculum for young children. In An Integrated Play-Based Curriculum for Young Children. https://doi.org/10.4324/9780203833278 Stufflebeam, D. L. (2003). The CIPP model for evaluation. In Oregon Program Evaluators Network (pp. 31–62). https://doi.org/doi:10.1007/978-94-010-0309-4_4 Sturgess, J. (2003). A model describing play as a child-chosen activity - Is this still valid in contemporary Australia? Australian Occupational Therapy Journal, 50(2), 104–108. https://doi.org/10.1046/j.1440-1630.2003.00362.x Taylor, M. E., & Boyer, W. (2020). Play-Based Learning: Evidence-Based Research to Improve Children’s Learning Experiences in the Kindergarten Classroom. Early Childhood Education Journal, 48(2), 127–133. https://doi.org/10.1007/s10643-019-00989-7 Thompson, G. (2013). NAPLAN, myschool and accountability: Teacher perceptions of the effects of testing. International Education Journal, 12(2), 62–84. van Oers, B. (2012). Developmental education for young children: Concept, practice and implementation. Developmental Education for Young Children: Concept, Practice and Implementation, 1–302. https://doi.org/10.1007/978-94-007-4617-6 van Oers, B. (2015). Implementing a play-based curriculum: Fostering teacher agency in primary school. Learning, Culture and Social Interaction, 4, 19–27. https://doi.org/10.1016/j.lcsi.2014.07.003 van Oers, B., & Duijkers, D. (2013). Teaching in a play-based curriculum: Theory, practice and evidence of developmental education for young children. Journal of Curriculum Studies, 45(4), 511–534. https://doi.org/10.1080/00220272.2011.637182 Wallerstedt, C., & Pramling, N. (2012). Learning to play in a goal-directed practice. Early Years, 32(1), 5–15. https://doi.org/10.1080/09575146.2011.593028 Weisberg, D. S., Zosh, J. M., Hirsh-Pasek, K., & Golinkoff, R. M. (2013). Talking it up: Play, langauge, and the role of adult support. American Journal of Play, 6(1), 39–54. Retrieved from http://www.journalofplay.org/issues/6/1/article/3-talking-it-play-language- development-and-role-adult-support Wong, S. M., Wang, Z., & Cheng, D. (2011). A play-based curriculum: Hong Kong children’s perception of play and non-play. International Journal of Learning, 17(10), 165–180. https://doi.org/10.18848/1447-9494/cgp/v17i10/47298